Zakat sebagai Instrumen Dakwah: Strategi Kedermawanan dalam Menggerakkan Perubahan Sosial - Alia, Rukmana Nada; Nurhaura, Fania Nazla; Cahyo, Aryo Adi; Nuraidin, Novit; Farhani, Wafiq Alfi; Salsabila, Flora; Rofiq, Nur (Fakultas Dakwah UIN KHAS Jember, 2024)
Zakat has a strong legal foundation in Islam and holds the potential to serve as both a da'wah instrument and an effective generosity strategy in driving social change. However, in practice, zakat management still faces various challenges, such as low public awareness in fulfilling zakat obligations and inefficient distribution. This study aims to analyze the role of zakat as a da'wah instrument from an Islamic perspective and evaluate the implementation of zakat generosity strategies in promoting social change. The research employs a normative approach with a literature review methodology, encompassing conceptual analysis and empirical studies from various academic sources. The findings indicate that zakat has a significant impact on spiritual, social, and economic aspects. It enhances religious awareness, strengthens social solidarity, and serves as an instrument of economic justice. Additionally, zakat-based generosity strategies have proven effective in alleviating poverty and improving community welfare, especially when managed professionally with appropriate communication strategies. However, optimizing zakat as a tool for social transformation requires further innovation in management and collaboration with various stakeholders. Thus, zakat can become a more effective instrument in fostering sustainable societal well-being.